PERANAN PEMBIMBING KEMASYARAKATAN DI BALAI PEMASYARAKATAN KELAS II SAMARINDA DALAM PROSES DIVERSI - Denny Aditia Kusuma (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACT This research aims to know the extent of  the role of Pembimbing Kemasyarakatan at Balai Pemasyarakatan Kelas II Samarinda in the process diversion to Children in Conflict with The Law and to know the factor and to determine the factors that hinder the implementation of the Diversion and Diversi and any legal consequences arising if the Diversion can not be implemented as it should be based to Undang-Undang Nomor 11 Tahun 2012 tentang Sistem Peradilan Pidana Anak.Author to achieve these objectives using such data collection techniques in the form of research literature and  field studies by conducting direct intervews with related parties, that is Pembimbing Kemasyarakatan Klien Anak at Balai Pemasyarakatan Kelas II SamarindaBased on the results of research conducted, the role of Pembimbing Kemasyarakatan is very important in the implementation of Diversion by doing assistance and guidance to Children in Conflict with The Law and found several factors that inhibit the Pembimbing Kemasyarakatan in the process of Diversion, that is : lack of facilities and infrastructure, weak coordination among agencies dealing with the problem of the Children in Conflict with The Law, the limited number of Pembimbing Kemasyarakatan, a lack of public understanding about the diversion and determination agreement on the restitution.If the attempt fails, the Diversion legal consequencies arising for Children in Conflict with The Law is imprisonment then to Investigator, Prosecutor and Judge which in the case of child des not seek the process of Diversion shall be sanctioned with a penalty of imprisonment of  2 (two) years or maksimum fine  Rp 200.000.000,- (two hundred million rupiahs) as regulated in Pasal 96 Undang-Undang Nomor 11 Tahun 2012 Tentang Sistem Peradilan Pidana Anak. Keywords: Pembimbing Kemasyarakatan, Diversion, Child Criminal Justice